Znaczenie strumieni finansowych w gospodarce wysoko rozwiniętych państw kapitalistycznych - Kowalczyk, Zygmunt (Wydział Prawa i Administracji UAM, 1972)
The role of financial phenomena is growing with economic development at the cost of material phenomena. Capitalistic states interfere into economic affairs of the country mainly by means of financial instruments. The state is a kind of generator of financial flows and affects financial flows of other economic subjects (so called creative and redistributive effect of the state). The interrelation of financial flows and material infrastructure of national economy can be measured by help of the FIR, i.e. the ratio of the total of financial flows in a given time to the gross national product in the time. In connection with the quantitative and qualitative growth of financial flows the thesis has been put forward that it is an anachronism to distinguish into „monetary" and „financial" elements and „real" and „financial" ones. The role of financial intermediaries i.e. banks and other numerous financial bodies in directing the financial flows has been growing. A general theory of financial structure of capitalistic countries has not been formed yet.
The Importance of Financial Flows in the Economy of Developed Capitalistic Countries